Measuring the Volatility and Market Efficiency of The Brazilian Market from 2006-2010 - Sergeant, Brent (2011)
ABSTRACT Emerging market countries play an ever important role in global capital markets, through international diversification and new investment opportunities. However, the increase in global capital invested in emerging markets is fractional when compared to the levels of investment attributed to developed nations. The lack of transparency into emerging markets has affected investors understanding of how efficient emerging markets are. Furthermore, the affects of volatility within these regions is under investigated topic within financial literature, and tends to leave investors sceptical when allocating their capital into these regions. Meccabni & Sourial (1999) research paper for the International Monetary Fund (IMF), tries to address these questions, by carrying out individual studies of volatility and market efficiency on the Egyptian market, in the attempt to explain the dynamics and characteristics of emerging markets. Similar to this, the objective of this investigation is to model the volatility and analyse the market efficiency for the Brazilian market, over the recent financial crisis. Using the (G)ARCH(p,q) conditional volatility models to estimate volatility; and unit root tests and the Autocorrelation Function (ACF) to analyse the market efficiency, this study aims to explain and characterise the dynamics of the Brazilian market over the crisis. The results show that the Brazilian market periods of persistence of the returns with regards the shocks in the local market, and with regards to the efficiency, we find the market returns pointed towards relative efficiency of the local market.